Contrasting the anti-vaccine prejudice: a public health perspective - Paola Stefanelli; Giovanni Rezza (Istituto Superiore di Sanità, 2014)
Although immunization is one of the most successful and cost-effective health interventions, there has been always opposition to vaccines. This may be due to several factors, some of which are : 1) the vaccines are given to healthy individuals to prevent disease; 2) the perception of the vaccine value paradoxically declines when the use of a vaccine reduces or eliminates the risk of a disease. Contrasting anti-vaccine movements/ feelings is important in order to keep vaccinate coverage rates high. Specific training of health care workers and other vaccine providers is needed in order to understand the reasons of reluctant parents, and to deal with prejudice and misinformation.